Camel Milk Mitigates Cyclosporine-Induced Renal Damage in Rats: Targeting p38/ERK/JNK MAPKs, NF-κB, and Matrix Metalloproteinases - Arab, Hany H. (Biology (Basel), 2021)
SIMPLE SUMMARY: The widespread use of the immunosuppressant cyclosporine A in organ transplantation and autoimmune disorders has been associated with renal damage as an adverse effect. The present work aimed to examine the potential of camel milk, a natural agent with marked anti-inflammatory/antioxidant properties, to mitigate cyclosporine-induced renal injury. The present findings revealed that cyclosporine A induced severe renal damage in rats, as indicated by the increased levels of nephrotoxicity markers (serum creatinine, blood urea nitrogen, and kidney injury molecule 1). Moreover, cyclosporine A triggered a marked renal inflammation, as seen by increased renal pro-inflammatory cytokines (e.g., tumor necrosis factor-alpha, interleukin-1 beta, and interleukin-18), renal degradation enzymes (matrix metalloproteinases-2 and -9), and activation of renal inflammatory signaling pathways (mitogen-activated protein kinases and nuclear factor kappa B pathways). Furthermore, cyclosporine A instigated renal oxidative reactions and lowered the renal antioxidant defenses. Interestingly, camel milk (10 mL/kg/day; for 3 weeks by oral route) mitigated the aforementioned nephrotoxicity markers, pro-inflammatory cytokines, degradation enzymes, inflammatory pathways, oxidative stress, and augmented the renal antioxidant capacity. In conclusion, camel milk may be a promising natural agent that can inhibit cyclosporine-triggered renal damage. ABSTRACT: Renal damage is a devastating adverse effect for cyclosporine; a widely used immunosuppressant drug. The present work examined the potential of camel milk, a natural agent with marked anti-inflammatory/antioxidant properties, to attenuate cyclosporine-induced renal injury. The kidney tissue was examined with the aid of Western blotting, immunohistochemistry, biochemical assays, including colorimetric and ELISA kits. The present findings revealed that camel milk (10 mL/kg/day; for 3 weeks by gavage) significantly lowered serum creatinine, BUN, and KIM-1 renal dysfunction markers. Mechanistically, camel milk inhibited renal inflammation, as seen by significant decrease of the pro-inflammatory cytokines (MCP-1, TNF-α, IL-1β, and IL-18) and extracellular degradation signals (MMP-2 and MMP-9) and enhanced the generation of the anti-inflammatory IL-10. Moreover, it inhibited the upstream pro-inflammatory p38/ERK/JNK MAPK pathway by lowering the phosphorylation of the 3 subfamilies of MAPKs (p38 MAPK, JNK1/2, and ERK1/2). Furthermore, camel milk curbed the NF-κB pathway activation by downregulating the protein expression of activated NF-κBp65, p-NF-κBp65, and p-IκBα proteins. Additionally, camel milk inhibited renal oxidative stress by lowering the MPO activity and augmenting the reduced/oxidized glutathione ratio and total antioxidant capacity. These findings propose that camel milk may be a promising agent that inhibits cyclosporine-triggered renal inflammation via curtailing the p38/ERK/JNK MAPK and NF-κB pathways, matrix metalloproteinases, and pro-inflammatory cytokines.